(untitled) (Research, Society and Development, 2022)
The oil extracted from different oleaginous raw materials is usually obtained through mechanical pressing, associated or not with organic solvents. The objective of this prospection was to evaluate if the aqueous enzymatic extraction (AEE) with ultrasound should be a cleaner and more effective technology for the production of lipids and other products. The state of the art of this issue was observed with a focus on food, and more precisely oleaginous fruits and seeds. The advanced search in the Science Direct, Scopus and Web of Science (WOS) databases was carried out in July 2021. A total of 1,099, 79, and 46 scientific papers were retrieved within the Science Direct, WOS and Scopus databases, respectively. Identifying the experiments made in these studies with EAE and ultrasound, there was a selection of 24, 13 and 4 original articles in the investigated bases. The articles described that ultrasound used as pre-treatment or during AEE increased the yield of food lipid extraction. This prospection described that EAE technology and ultrasound are impactful techniques in obtaining lipids. The advanced research highlighted that there is a gap related to researches with oleaginous matrices and the replacement of conventional techniques with clean techniques can be economically feasible.